Arcyriaflavin A, a cyclin D1/CDK4 inhibitor, suppresses tumor growth, migration, and invasion of metastatic melanoma cells - Dokyeong Kim; Junseong Park; Yoon-Seob Kim; Okcho Na; Minyoung Park; Songzi Zhang; Sumin Cho; Yeun-Jun Chung (Cancer Cell International)
Abstract Background Despite advancements in targeted therapy and immunotherapy, cutaneous melanoma continues to have a high mortality rate and poor prognosis, with therapies having limited efficacy in advanced melanoma. Therefore, it is crucial to develop novel therapeutics with proven clinical potential. In this study, we evaluated the efficacy of arcyriaflavin A (ArcA), a potent inhibitor of the cyclin D1/CDK4 complex, in suppressing aggressive phenotypes of metastatic melanoma. Methods The effects of ArcA on viability and cell cycle were evaluated across four melanoma cell lines: WM239A and its metastatic derivatives: 113–6/4L, 131/4-5B1, and 131/4-5B2. Additionally, we performed wound healing and transwell invasion assays, followed by western blot. We further established xenograft mouse models by subcutaneously injecting them with the four melanoma cell lines and measured tumor size and weight biweekly. Immunohistochemistry analysis was performed to compare protein expression. Results ArcA demonstrated dose-dependent cytotoxicity, selectively targeting melanoma cells without affecting normal cells, and induced G1 cell cycle arrest. Moreover, ArcA significantly inhibited cell migration and invasion in metastatic melanoma cell lines, accompanied by reduced expression levels of p-GSK-3β (Ser9), MMP-9, and MMP-13, suggesting that its anti-metastatic effects may be partially mediated through GSK-3β, MMP-9, and MMP-13. These findings were further validated using mouse xenograft models; ArcA-treated mice exhibited significantly smaller tumor volumes and lighter tumor weights compared to vehicle-treated mice. Immunohistochemistry further confirmed decreased expression of p-GSK-3β, MMP-9, and MMP-13 in tumor tissues from ArcA-treated mice. Conclusions Collectively, our findings indicate that ArcA possesses substantial anti-tumor potential, including cytotoxic effects and inhibition of migration and invasion in metastatic melanoma. These results suggest that ArcA could enhance therapeutic efficacy in the treatment of metastatic melanoma.